IMPLEMENTATION OF THE SMART BUILDING CONCEPT IN PARAHYANGAN OFFICE RENTAL SPACE AND APARTMENT DESIGN - Nurrahman, Hafiz; Permana, Asep Yudi; Susanti, Indah (Universitas Pendidikan Indonesia, 2021)
The design of Parahyangan Office Rental Space and Apartment is intended to create offices and residential areas that accommodate business and residential functions with the concept of smart building applied to various aspects of architectural design. Parahyangan Office Rental Space and Apartment is the offices and residential areas that accommodate the needs of community in Kota Baru Parahyangan, not only in business activities but also in residence. In this area, the offices become a place for business and economic activities for the people of Kota Baru Parahyangan and its surroundings. Moreover, the offices also become the biggest business center and office center in Kota Baru Parahyangan and/or Bandung Regency and its surroundings. Meanwhile, the residential areas are the place for the emergence of vertical residential needs in Kota Baru Parahyangan. The Smart building concept is chosen because of the need for efficiency in activities. Living in urban areas requires a high level of mobility and movement, which can be supported using the smart building concept. The system of buildings, in which the occupants live and do their activities, can be set through the intelligent building, so that residents can allocate their time and energy to other things. Smart building can also generate comfortable, productive, and simpler life for residents of the building.Keywords: Smart Building, Office, Residence